New media, new relations: cyberstalking on social media in the interaction of Muslim scholars and the public in West Sumatra, Indonesia - Syahputra, Iswandi (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article explains how the presence of social media as one of the forms of new media has prompted changes in the relations and communications between ulama and the public. The relationship between ulama, religious teachings, and the ummah (Muslim community/the public) undoubtedly undergoes constant changes. In the current era of new media, this relationship experiences mediatization of differing features compared to past era of traditional media. The era of new media ushered in participative, open, interactive characteristics encouraging development of virtual communities, and interconnectedness, consequently positioning ulama in two particular positions. Firstly, ulama have full control over the contents they intend to post and the choice of whom they wish to communicate with on social media. Secondly, due to the aforementioned characteristics of social media, ulama who actively post religious contents on social media had come to experience cyberstalking. Despite having to endure and suffer from cyberstalking, the ulama remained active on social media and continued posting religious contents as they consider social media to have numerous positive values beneficial to spreading good values and religious teachings to the wider public. The research findings show that social media as a form of new media has led to the emergence of new relations that are entirely unlike previous traditional media. The research data were collected through in-depth interviews with three Muslim scholars of West Sumatra who are active on social media and have extensive social influences.